Why do gun murders have a higher clearance rate than gunshot assaults? - Cook, Philip J. (Criminology & public policy, 2019)
The prevailing view is that follow‐up investigations are of limited value as crimes are primarily cleared by patrol officers making on‐scene arrests and through the presence of eyewitnesses and forensic evidence at the initial crime scene. We use a quasi‐experimental design to compare investigative resources invested in clearing gun homicide cases relative to nonfatal gun assaults in Boston. We find the large gap in clearances (43% for gun murders vs. 19% for nonfatal gun assaults) is primarily a result of sustained investigative effort in homicide cases made after the first 2 days.